Faktor-Faktor Yang Mempengaruhi Financial Distress pada Perusahaan Non Keuangan - Gunawan, James Tirta; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to obtain empirical evidence about the effects of sales growth, operating capacity, and cash flow on financial distress. The sample in this study was selected using purposive sampling method amounted to 31 non finance companies listed on the Indonesia Stock Exchange (IDX) within 2018-2020 that match the criteria. The data processing technique using logistic regression analysis assisted by the EViews 12 program. The results of this study indicate that sales growth has no effect on financial distress, while operating capacity has a negative and significant effect on financial distress, and cash flow has no effect on financial distress.